“On the street, the only person you gotta bow down to is yourself”: Masculinity, homelessness, and incarceration - Umamaheswar, Janani (Justice Quarterly, 2021)
Despite the well-established link between homelessness and incarceration, very little qualitative research has focused on the social processes that underlie this nexus. In this article, I draw on 19 in-depth interviews with incarcerated men who reported pre-prison housing instability, supplemented with 5 interviews with formerly-incarcerated men experiencing homelessness, to explore the gendered nature of the homelessness-incarceration nexus. I propose the concept of “liberative instability”—defined as an unfettered lifestyle characterized by double-edged freedom and independence—to explore the changing meaning of homelessness in men’s narratives of their life course. Additionally, I explore how themes of masculinity and liberative instability are embedded in men’s narratives of freedom and confinement as they reflect on their experiences with homelessness and incarceration. These findings animate existing quantitative research by highlighting that the homelessness-incarceration nexus cannot be understood fully or disrupted without considering the significance of age-graded cultural scripts regarding masculinity. © 2021 Academy of Criminal Justice Sciences.
1 citations (Crossref) [2023-10-31]
Keywords: Homelessness; dept.soc; incarceration; masculinity; peer-reviewed; the life course

‘Suppression on top of oppression’: A symbolic interactionist perspective on the affective experience of incarceration - Umamaheswar, Janani (The British Journal of Criminology, 2021)
Penological research has extensively documented how incarcerated men's identities are shaped by the prison setting, highlighting how these men cope with and adapt to the 'pains of imprisonment' through careful emotion management. Significantly less research has focused explicitly on the role of emotion in incarcerated men's constructions of their selves. In this article, I draw on 24 in-depth interviews with incarcerated men to reveal how the prison setting generates negative emotions (such as sadness, shame, humiliation, and anger) that in turn perpetuate the isolation that these men face. Emotions thus constitute an overlooked source of these men's social marginalization. Additionally, I draw on theoretical literature derived from symbolic interactionism (and identity theory in particular) to explore how participants cope with, and make efforts to overcome, their negative emotions by engaging in active emotion and identity work centred on constructing morality narratives of pride, self-worth, and superiority. © 2021 The Author(s) 2021. Published by Oxford University Press on behalf of the Centre for Crime and Justice Studies (ISTD). All rights reserved.
5 citations (Crossref) [2023-10-31]
Keywords: dept.swk; peer-reviewed